Peningkatan Motivasi dalam Mengelola Potensi Diri Menuju Pribadi Yang Berkualitas (Panti Sosial Bina Remaja Tarunajaya II) - Deasy Aseanty; Willy Arafah; Wulansari (PT FORMOSA CENDEKIA GLOBAL, 2022)
The process of self-development can be realized by managing the individual's potential. This will affect with individual motivation. A motivation that has not been realized, of course, this needs to be known. One way to realize one's motivation is how effective and efficient the management of oneself and the environment is of each individual. Self-management is what we call action management. The word management has a deep meaning, that is, it starts with setting a plan to be achieved (i.e setting goals, setting the design and structure of the company, carrying out activities and evaluating work).